Diversidade funcional e negra de isópodes subterrâneos em áreas cársticas do centro-leste do Brasil - Fernandes, Camile Sorbo (Universidade Federal de São Carlos, 2015)
We addressed the mechanisms responsible for the composition of subterranean communities and its consequences for the maintenance of ecological processes. In the first chapter, we tested whether cave communities were assembled by the restrictive regime propitiated by permanent darkness, or by limiting similarity caused by competitive exclusion when compared to surface communities. With this purpose, we measured several niche descriptors of species from inside and outside caves using a multivariate measure of functional diversity and compared their widths. Our results showed that isopods found inside caves favourable conditions to allow occupation and diversification, with milder environmental parameters coupled with the absence of specialised predators. There is, therefore, phenotypic overdispersion and higher functional diversity in cave species when compared to surface ones. This higher functional diversity results in better efficiency in resource use, but also in lower resilience of ecological processes. In the second chapter, we tried to understand the processes underlying patterns of subterranean biodiversity and its consequences, because species do not occur in all caves or habitat patches where their occurrences are expected. We looked for the species absences, known as the dark diversity, for estimation of how much of the habitat-specific regional species pool is realised within each local cave community. We tested whether the species were absent because of their functional attributes and tried to understand the relative importance of determinants of cave biodiversity using local-regional regression models. Our results indicated that the occurrence of the species is far from its potential, considering habitat availability and ecological requirements. We found no relationship between species absences and functional traits but this is possibly an artifact of the low species number and low co-occurrences of isopods. For the same reason the regression models did not fit in the local-regional relationship. Differences between caves and regions possibly results from the amount of microhabitats, resource inputs and historical factors and, from a conservation perspective, the caves with higher completeness deserve attention, because they may be a source of migratory individuals to other areas in the vicinity. In the third chapter we compiled the current state of knowledge of oniscidean fauna in Brazilian caves by listing the described species and adding several new records from our own surveys. Among these, certainly new species will be identified. We also addressed the need of validation of the new species and identification of the unrecognized ones by proper taxonomic research, as any delay may yield loss of biodiversity.
Keywords: Cavernas; Isopoda; Regras de assembleia; Serra do Ramalho; São Desidério; São Domingos; Caves; Isopoda; Assembly rules; Serra do Ramalho; São Desidério; São Domingos; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS